Integration of the Numbered Heads Together Model and Audiovisual Media in Social Studies: Strengthening Character Education in Elementary Schools - Muhammad Nawir; Darmawati Darmawati; Jumriati Jumriati (International Journal of Nusantara Islam, 2026)
This article examines the effectiveness of integrating the Numbered Heads Together (NHT) cooperative learning model with audio-visual media in social studies to boost learning outcomes and character development among 60 fifth-grade students at Elementary School Cluster 1, Takalar Regency, South Sulawesi, Indonesia. Using a quantitative experimental design with pre-test/post-test control groups, the experimental group (NHT + audio-visual) outperformed the control (conventional methods), achieving a mean post-test score of 82.4 vs. 66.3 (p < 0.05). Observations showed enhanced participation, collaboration, accountability, critical thinking, and social skills. This approach fosters a dynamic environment for cognitive, moral, and social growth, emphasizing teacher training and tech infrastructure.